2002
DOI: 10.1067/mtc.2002.120333
|View full text |Cite
|
Sign up to set email alerts
|

Failure of retrograde cerebral perfusion to attenuate metabolic changes associated with hypothermic circulatory arrest

Abstract: Retrograde cerebral perfusion did not influence immediate post-arrest nasopharyngeal temperature or cerebral metabolic recovery. The low jugular bulb Po(2) suggests equivalent ischemia. These findings cast doubt on the effectiveness of retrograde cerebral perfusion as a metabolic adjunct to hypothermic circulatory arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 44 publications
1
42
0
3
Order By: Relevance
“…ScO 2 was monitored with near infrared spectroscopy in all cases. A number of studies have shown that RCP may not provide enough oxygen to the brain during DHCA (27)(28)(29)(30), which is consistent with the current findings although the two groups had a similar incidence of postoperative delirium. In group 1, the decrease in ScO 2 during CPB was not related to the occurrence of postoperative delirium.…”
Section: Pi and Ri Of Ica And Ecasupporting
confidence: 83%
“…ScO 2 was monitored with near infrared spectroscopy in all cases. A number of studies have shown that RCP may not provide enough oxygen to the brain during DHCA (27)(28)(29)(30), which is consistent with the current findings although the two groups had a similar incidence of postoperative delirium. In group 1, the decrease in ScO 2 during CPB was not related to the occurrence of postoperative delirium.…”
Section: Pi and Ri Of Ica And Ecasupporting
confidence: 83%
“…17 Data were computer- stored on a commercial database and analyzed using SPSS 11.0 for Windows. Categorical data were compared using 2 or Fisher exact tests as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiopulmonary bypass (CPB) management was performed according to our previous protocol. 17 Flows were maintained at 2.4 L/min per m 2 during normothermia and reduced to 1.6 L/min per m 2 at 15°C. A mean systemic blood pressure of 55 to 70 mm Hg was maintained using alpha agonists or glyceryl trinitrate as necessary.…”
Section: Anesthetic and Perfusion Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the period of DHCA has been completed and cerebral reperfusion has been initiated, severe cerebral vasoconstriction occurs. There is also an accumulated cerebral oxygen debt from the ischemic period which must be "paid back", and therefore, normal levels of cerebral metabolism are maintained by increased oxygen extraction (10,11,12). During the period following DHCA, the brain is at high risk for both ongoing ischemic injury due to low cerebral blood flow, and reperfusion injury.…”
Section: Wwwintechopencommentioning
confidence: 99%